The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s12098-007-0203-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of environmental tobacco smoke exposure among adolescents in Mangolia

Abstract: Exposure to environmental tobacco smoke is high among school going adolescents in Mongolia. Public health interventions aimed to reduce morbidity from tobacco among adolescents should also accord particular attention toward environmental tobacco smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 25 publications
5
25
2
Order By: Relevance
“…This finding is in line with results of other relevant studies worldwide 12,13 . Exposure at home increased significantly with age, which is in agreement with the results of the study by Rachiotis et al 2010.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with results of other relevant studies worldwide 12,13 . Exposure at home increased significantly with age, which is in agreement with the results of the study by Rachiotis et al 2010.…”
Section: Discussionsupporting
confidence: 93%
“…However, they have to continue to be exposed to SHS (especially at home) because they do not have choices. The study did not find any gender and age group differences regarding exposure to SHS, which was also found in a study among Puerto Rican children [14], but other studies found higher exposure to SHS with increasing age and among males [4,6]. …”
Section: Discussionsupporting
confidence: 58%
“…Exposure to SHS in children contributes significantly to morbidity and mortality [1,3]. Gender, age group, parental and close friends smoking status [2,46], and low perceived susceptibility [7] were found to be significantly associated with adolescent’s exposure to SHS.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in line with that of Rudatsikira et al . among adolescents in Mongolia who reported that increasing age was associated with higher likelihood of being exposed to environmental tobacco smoke in both sexes [9]. However, the finding contradicts that of Preston et al .…”
Section: Discussionmentioning
confidence: 94%